Multidrug-resistant Staphylococcus chromogenes pyoderma in Rattus norvegicus: case report - Tronca, Julia Facchin; Silva, Felipe Esteves da; Piccinini, Alessandra Gugel; Damin , Vitória; Brambatti, Gustavo; Prusch, Fabiane; Streck, André Felipe (Medicina Veterinária, 2024)
This case study investigated a multidrug-resistant Staphylococcus pyoderma infection in a pet Rattus norvegicus. The clinical presentation involved a range of clinical signs, including pruritus, inflammation, pustules, and crusts on the skin, indicative of bacterial pyoderma. Conventional and molecular techniques were used, and the pathogen was identified as Staphylococcus chromogenes. The suspected transmission route was through a bite from another rat, although the aggressor was not tested. Initial treatment with enrofloxacin proved ineffective. Subsequently, an amoxicillin + potassium clavulanate treatment resulted in temporary improvement. Nevertheless, the infection relapsed after 30 days, necessitating a repeated course of treatment. The findings underscore the importance of accurate diagnosis, appropriate testing, and adherence to prescribed treatments for bacterial infections. The zoonotic potential of multidrug-resistant Staphylococcus highlights the need for better education of pet owners on transmission risks and treatment compliance. Additional research is essential to explore the transmission routes of this infection, the potential risks to pet owners, and to gain a more comprehensive understanding of Staphylococcus chromogenes pyoderma in domestic rodents.